Wide dynamic range linear‐logarithmic CMOS image sensor using photogate and cascode MOSFET. Issue 3 (5th December 2016) - Bae, M.; Jo, S.‐H.; Choi, B.‐S.; Lee, H.H.; Choi, P.; Shin, J.‐K.
Abstract : A wide dynamic range CMOS image sensor is proposed, exhibiting a linear response at a low illumination level and a logarithmic response at a high illumination level. To maintain high sensitivity and to improve the dynamic range of the proposed pixel, a cascode MOSFET is integrated into the structure of the proposed pixel, along with a photogate. The applied photogate voltage reduces the sensitivity of the proposed pixel under the linear response regime, at a moderate illumination level. Under high illumination levels, the biased cascode MOSFET serves as a voltage‐light‐dependent active load and is responsible for logarithmic operation. The dynamic range of the proposed pixel can be improved by adjusting the sensitivity and the basis of the logarithmic response.